Lumi Interactive Educational Media Based On H5P For Students' Critical Thinking Skills In Elementary Schools - Wini Citra Lestari; Ghullam Hamdu; Syarif Hidayat (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
The ability to think critically is very important to be raised from an early age. The changing times as evidenced by the rapid development of technology can be utilized in education. H5P-based Lumi Education is one of the interactive media that can be used. However, a clear and in-depth study is needed to prove its effectiveness, before it will be applied thoroughly by educators. This study aims to examine the effectiveness of H5P-based Lumi Education interactive media in developing students' critical thinking skills in elementary schools through a literature study approach. The results of the review of various sources of scientific literature show that the use of H5P interactive media can increase students' motivation, engagement, and critical thinking skills. Interactive features such as quizzes, drag-and-drop, and interactive videos trigger deeper thinking activities. The Lumi Education platform also supports independent and reflective learning which is an important part of developing critical thinking skills. In addition, the conformity of this media with the principles of the Curriculum shows its relevance in the current educational context. Nevertheless, the effectiveness of this media is influenced by the readiness of teachers in designing content as well as the availability of supporting infrastructure. Thus, H5P-based Lumi Education has the potential as an innovative learning media to encourage learners' critical thinking skills from an early age.